2019
DOI: 10.1016/j.envres.2019.108614
|View full text |Cite
|
Sign up to set email alerts
|

A remote sensing emissions monitoring programme reduces emissions of gasoline and LPG vehicles

Abstract: Vehicle emissions are a major source of air pollution in Hong Kong affecting human health. A 'strengthened emissions control of gasoline and liquefied petroleum gas (LPG) vehicles' programme has been operating in Hong Kong since September 2014 utilising remote sensing (RS) technology. RS has provided measurement data to successfully identify high emitting gasoline and LPG vehicles which then need to be repaired or removed from the on-road vehicle fleet. This paper aims to evaluate the effectiveness of this glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The above studies observed opposite NO emission trends due to the different fuel types concerned, i.e. gasoline and LPG vehicles in Bishop and Haugen (2018); Organ et al (2019) vs diesel vehicles in Huang et al (2018c); Pujadas et al (2017). RS studies showed that gasoline NOx reduced obviously in the past 15-20 years but diesel NOx did not reduce over the same period including those vehicles equipped with exhaust after-treatment systems for NOx control (Carslaw and Rhys-Tyler, 2013;Chen and Borken-Kleefeld, 2014).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The above studies observed opposite NO emission trends due to the different fuel types concerned, i.e. gasoline and LPG vehicles in Bishop and Haugen (2018); Organ et al (2019) vs diesel vehicles in Huang et al (2018c); Pujadas et al (2017). RS studies showed that gasoline NOx reduced obviously in the past 15-20 years but diesel NOx did not reduce over the same period including those vehicles equipped with exhaust after-treatment systems for NOx control (Carslaw and Rhys-Tyler, 2013;Chen and Borken-Kleefeld, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…RS can measure the emissions of a large number of vehicles over a short time, which are widely used to examine the emission trends as a result of various factors, such as more stringent vehicle emission standards (Carslaw et al, 2011;Chen and Borken-Kleefeld, 2014;Lau et al, 2012;Pujadas et al, 2017), engine technology advancement (Huang et al, 2018c;Sjödin, 1994), engine deterioration (Borken-Kleefeld and Chen, 2015;Chen and Borken-Kleefeld, 2016) and other vehicle emission control programs such as fleet renewal and inspection and maintenance (I/M) programs (Bishop et al, 2013;Bishop et al, 2012;Organ et al, 2019;Stedman et al, 1997). These studies all used only one set of RS system.…”
Section: Effect Of Sample Size On Emissions Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1 September 2014, the Hong Kong Environmental Protection Department (HKEPD) started using on-road remote sensing technology to detect high-emitting petrol and liquefied petroleum gas (LPG) vehicles for enforcement (HKEPD, 2018). The enforcement program has been very effective in reducing the emissions from petrol and LPG vehicles (Huang et al, 2018b;Organ et al, 2019). However, diesel vehicles, a major source of NOx emissions, are excluded because the current remote sensing system would likely produce significant false detections of diesel high-emitters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, developing electric and hybrid electric vehicles to improve engine fuel efficiency, and autonomous vehicles to improve eco-traffic. Optimizing traffic management measures is mainly about intelligent traffic control methods [24][25][26][27][28]. The research shows that reducing the delay time and the number of stops at intersections by controlling traffic signals on an urban route network can reduce vehicle emissions [27].…”
Section: Introductionmentioning
confidence: 99%